Die christlich-abendländische Wahrnehmung anderer Religionen im frühen und hohen Mittelalter : Methodische und Vergleichende Aspekte - Goetz, Hans-Werner (Wolfgang Stammler Gastprofessur für Germanische Philologie - Vorträge, 2013)
Until now, the ways that Medieval Catholic Christianity perceived other religions (Paganism, Islam, Judaism) has never been the subject of a systematic and comparative study. This publication, which emerged from a project funded by the European Research Council, brings together important research findings to compare Christian perceptions of other religions. It also opens up new perspectives on Christian self-understanding.